Analysis of The Use Of Transportation Modes in Crude Oil Distribution at PT BBS Bojonegoro - Tri Warcono Adi; Nano Koes Ardhiynto; Nur Ardiansah; Muhammad Rafwal (Institut Teknologi Adhi Tama Surabaya, 2025)
Indonesia, as a country rich in natural resources, has a very diverse mining sector, including oil and gas mining. In an effort to increase national oil production and improve the standard of living and welfare of the community, regulations are needed to regulate the management and business of oil. Regulation of the Minister of Energy and Mineral Resources No. 01 of 2008 concerning Guidelines for the Business of Oil Mining in Old Wells. This regulation is considered an implementation of the principles contained in Article 33 of the 1945 Constitution and provides positive support for Regional Governments that have many old wells. The regulation opens up opportunities for increasing Regional Original Income (PAD) and community welfare through the participation of Village Unit Cooperatives (KUD) or Regionally-Owned Enterprises (BUMD) in oil production in old wells in their areas. In addition, in the distribution of oil, this mode of transportation is also an important aspect for Village Unit Cooperatives (KUD) or Regionally-Owned Enterprises (BUMD) in the Bojonegoro Regency area, which, as one of the regencies in East Java Province, is an area that produces oil and gas that is still active to this day. Oil fields in Kedewan District, Bojonegoro Regency, are generally old fields that have been made since the Dutch era, so their production has decreased. Even so, the potential of old oil wells that have been closed can still be managed and utilized through traditional mining methods by involving local communities both in management and in the distribution of oil by land transportation from oil wells to storage areas in the work area of PT Pertamina EP Asset 4 Cepu Field. This study aims to obtain information about problems in the distribution of oil transportation from old wells to storage/reservoirs related to policies, regulations, infrastructure conditions, and their dynamics. The research methods that will be used involve observation, documentation, inventory, and interviews, with qualitative methods and thematic analysis. The results of this study are expected to produce outputs in the form of scientific articles or national journals.